Steam explosion processing intensifies the nutritional values of most crop byproducts: Morphological structure, carbohydrate-protein fractions, and rumen fermentation profile - He, Liwen; Huang, Yinchao; Shi, Lei; Zhou, Zhenming; Wu, Hao (Frontiers in Nutrition, 2022)
To investigate the feasibility of steam explosion on the exploitation of ruminant feedstuff, the morphological structure, carbohydrate-protein fractions, and rumen fermentation profile of five typical crop byproducts (corn cob, rice straw, peanut shell, millet stalk, and sugarcane tip) were analyzed before and after steam explosion processing. The results showed that these crop byproducts had different physicochemical properties and rumen fermentation profiles, most of which could be improved by steam explosion processing, i.e., more rough morphological surface, much-broken structure, more digestible carbohydrate fraction (non-NDF +49.92–452.24%), faster gas production rate (c +9.72–68.75%), higher dry matter digestibility (DMD48 +11.38–47.36%), more available energy (ME −3.69–+42.13%, except for peanut shell), along with more unavailable protein fraction (ADICP +27.16–102.70%). It is suggested that steam explosion processing could intensify the feeding value of most crop byproducts for ruminants, but with a caution of heat damage to proteins.